Integrating Chemistry and Mechanics: The Forces Driving Axon Growth - Franze, Kristian (Annual Reviews Inc., 2020)
The brain is our most complex organ. During development, neurons extend axons, which may grow over long distances along well-defined pathways to connect to distant targets. Our current understanding of axon pathfinding is largely based on chemical signaling by attractive and repulsive guidance cues. These cues instruct motile growth cones, the leading tips of growing axons, where to turn and where to stop. However, it is not chemical signals that cause motion-motion is driven by forces. Yet our current understanding of the mechanical regulation of axon growth is very limited. In this review, I discuss the origin of the cellular forces controlling axon growth and pathfinding, and how mechanical signals encountered by growing axons may be integrated with chemical signals. This mechanochemical cross talk is an important but often overlooked aspect of cell motility that has major implications for many physiological and pathological processes involving neuronal growth.
CRIS-Team Scopus Importer:2022-08-05
Keywords: forces; guidance; mechanosensitivity; mechanotransduction; neurons; pathfinding